Guidelines for future research in constraint‐induced movement therapy for children with unilateral cerebral palsy: an expert consensus. (8th October 2013) - Eliasson, Ann Christin; Krumlinde‐Sundholm, Lena; Gordon, Andrew M; Feys, Hilde; Klingels, Katrijn; Aarts, Pauline B M; Rameckers, Eugene; Autti‐Rämö, Ilona; Hoare, Brian
<x xml:space="preserve">Abstract</x> Aim The aim of this study was to provide an overview of what is known about constraint‐induced movement therapy (CIMT) in children with unilateral cerebral palsy (CP), to identify current knowledge gaps, and to provide suggestions for future research. Method Nine experts participated in a consensus meeting. A comprehensive literature search was conducted and data were summarized before the meeting. The core model produced by the European network for Health Technology Assessment was used as a framework for discussion and to identify critical issues for future research. Results All models of CIMT have demonstrated improvements in the upper limb abilities of children with unilateral CP. A consensus was reached on 11 important questions to be further explored in future studies. The areas of highest priority included the effect of dosage, the effect of repeated CIMT, and the impact of predictive factors, such as age, on the response to CIMT. Consensus suggestions for future study designs and the use of validated outcome measures were also provided. Interpretation The CIMT construct is complex, and much remains unknown. It is unclear whether a specific model of CIMT demonstrates superiority over others and whether dosage of training matters. Future research should build upon existing knowledge and aim to provide information that will help implement CIMT in various countries with different health care resources and organizational structures.